PENGARUH PENGETAHUAN ECO SCHOOL TERHADAP KEPUTUSAN PEMBELIAN GREEN PRODUCT PADA SISWA SMAN 9 SURABAYA - ULUMIYAH, AINUL (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Surabaya is the metropolitan to two in indonesia after Jakarta. Like other big cities Surabaya also under various environmental problems, one is waste matter. Therefore Surabaya have a great commitment to absolve oneself of waste problem, and become as green city. It was proven by various award gained Surabaya one is Indonesian Green the Region Award in 2011. Seriousness Surabaya in realizing behavior eco-friendly was supported by this schools environmentally friendly in surabaya. Research purposes this is to know whereabouts influence knowledge eco school of the decision purchase green product on the student of SMAN 9 surabaya. This research use approach quantitative by the number of samples taken as random 233 students SMAN 9 Surabaya who will be the goal the spread poll. By using analysis of data linear regression simple, this research result indicates that knowledge eco school influential significant of the decision purchase green product on the student of SMAN 9 Surabaya with an coefficient of determination 0,275. Influence what happens is a positive influence shown of the value of a coefficient of determination they positive and appertain low. This means more positive level knowledge eco school, the more affect decision purchase green product. Keyword: Knowledge Of Eco School, Decision Purchase, Green Product